POLA KONSUMSI PANGAN DAN ASUPAN ENERGI DAN ZAT GIZI ANAK STUNTING DAN TIDAK STUNTING 0—23 BULAN - Aslis Wirda Hayati; Hardinsyah Hardinsyah; Fasli Jalal; Siti Madanijah; Dodik Briawan (Jurnal Gizi dan Pangan, 2012)
ABSTRACTThe objectives of this study were to analyze food consumption, energy, and nutrients intake patterns between stunting and non-stunting in young children of 0—23 months old, using the data from BHR (Basic Health Research) 2010. The data sub-set from BHR 2010 was obtained into e-files form. From 6 634 under-two children 3 539 were screened out due to incompleteness, outlier, and unusual food consumption during data collection. Nutritional status data were processed using the WHO AnthroPlus 2007, while the other data/statistics were processed using the Excel and SPSS for windows. The different on food consumption pattern was performed with Man-Whitney U test. Food consumption, energy and nutrients intake patterns which measured were type number of food consumption, group number of food consumption, frequency of food consumption, nutrient adequacy, nutrient quality, and nutrients density. The results of study showed that analyze food consumption, and energy and nutrients intake patterns were different between stunting and non-stunting YC according to their age group; the higher the age, the higher their difference. There was no difference in food consumption, and energy and nutrients intake patterns between stunting and non-stunting children 0—5 months. Meanwhile, there was difference in children 6—11 and 12—23 months. The average of protein adequacy and protein density was difference between stunting and non-stunting children 6—11 months. In children 12—23 months, the differences not only in the average of protein adequacy and protein density but also in average of energy and calcium adequacy and calcium density, phosphor, vitamin A, and C adequacy, nutrient quality, and type number of food. Implications for Indonesia that is necessary to study the efficacy of nutritional interventions to achieving optimal linear growth in young children.Key words: children 0—23 months old, food pattern, stuntingABSTRAKPenelitian ini bertujuan menganalisis pola konsumsi pangan dan asupan energi dan gizi anak stunting dan tidak stunting 0—23 bulan menggunakan data Riskesdas 2010. Sub-set data Riskesdas 2010 diperoleh dalam bentuk e-files. Dari 6 634 data anak baduta dalam e-files Riskesdas 2010, sejumlah 3 539 data anak dikeluarkan karena data tidak lengkap, pencilan, konsumsi pangan saat kondisi tidak biasa. Status gizi diolah menggunakan WHO AntroPlus 2007, pengolahan data lainnya menggunakan program Microsoft Excel 2007 dan SPSS for windows. Uji beda pola konsumsi pangan menerapkan Mann-Whitney U test. Pola konsumsi pangan dan asupan energi dan zat gizi yang diukur berupa jumlah jenis konsumsi pangan, jumlah kelompok konsumsi pangan, frekuensi konsumsi pangan, tingkat kecukupan zat gizi, mutu gizi asupan pangan, dan densitas asupan zat gizi. Hasil kajian menunjukkan pola konsumsi pangan dan asupan energi dan zat gizi anak stunting dan tidak stunting 0—23 bulan berbeda menurut kelompok umur; semakin bertambah umur semakin meningkat perbedaannya. Pada anak 0—5 bulan tidak ada perbedaan pola konsumsi pangan dan asupan energi dan gizi anak stunting dan tidak stunting; sebaliknya pada anak 6—11 dan 12—23 bulan. Pada anak 6—11 bulan, rata-rata tingkat kecukupan protein anak stunting dan tidak stunting berbeda, demikian pula densitas asupan protein. Pada anak 12—23 bulan, tidak hanya rata-rata tingkat kecukupan protein dan densitas asupan protein, tetapi rata-rata tingkat kecukupan energi, tingkat kecukupan kalsium dan densitas asupan kalsium, tingkat kecukupan fosfor, tingkat kecukupan vitamin A, tingkat kecukupan vitamin C, mutu gizi makanan, dan bahkan jenis pangan juga berbeda. Implikasi untuk Indonesia yaitu perlu dilakukan penelitian efikasi intervensi zat gizi tersebut untuk pencapaian pertumbuhan linier optimal anak.Kata kunci: anak 0—23 bulan, pola konsumsi pangan, stunting